2014
DOI: 10.2214/ajr.13.11113
|View full text |Cite
|
Sign up to set email alerts
|

In-Phase Signal Intensity Loss in Solid Renal Masses on Dual-Echo Gradient-Echo MRI: Association With Malignancy and Pathologic Classification

Abstract: Visible in-phase signal intensity loss is relatively common within solid renal masses and was associated with RCC and particularly papillary RCC (among all RCCs) in our population. Quantitative analysis in lesions without visible signal intensity loss was not predictive of RCC. Further work should be performed to validate the usefulness of this additional imaging parameter to help characterize renal masses and to determine the impact of this finding on imaging techniques potentially sensitive to susceptibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
1
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 41 publications
4
25
1
1
Order By: Relevance
“…The greater the decrease in SI on in-phase images versus opposed-phase images, the more negative the value of the SI loss index was likely to be. The expected loss of SI related to the longer TE of the in-phase sequence was considered negligible in the present study, as has been reported in previously published studies [36,37]. Standardized ROI placement was used, rather than measurement of areas of a visible decrease in SI, to determine whether there is any additional benefit of quantitative versus subjective analysis.…”
Section: Quantitative Analysismentioning
confidence: 89%
See 3 more Smart Citations
“…The greater the decrease in SI on in-phase images versus opposed-phase images, the more negative the value of the SI loss index was likely to be. The expected loss of SI related to the longer TE of the in-phase sequence was considered negligible in the present study, as has been reported in previously published studies [36,37]. Standardized ROI placement was used, rather than measurement of areas of a visible decrease in SI, to determine whether there is any additional benefit of quantitative versus subjective analysis.…”
Section: Quantitative Analysismentioning
confidence: 89%
“…Yoshimitsu et al [36] first reported the use of chemical-shift MRI (i.e., detection of susceptibility artifact on the longer-TE in-phase image, compared with the shorter-TE opposed-phase image) as a finding associated with RCC and, in particular, with papillary RCC [36]. More recently, this finding was reevaluated by Childs et al [37], who also concluded that this finding was specific for RCC and that it was more common in papillary tumors, with histologic analysis confirming its association with the presence of intratumoral hemorrhage.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study suggests that the detection of intracellular hemosiderin with MRI is highly specific for the diagnosis of renal malignancies; in particular papillary RCCs [35]. Hemosiderin is characterized by relative signal loss within a tumor on in-phase MR images, and its detection obviates the need for biopsy (Fig.…”
Section: Renal Masses That Contain Hemosiderinmentioning
confidence: 99%